2004
DOI: 10.1002/jsfa.1820
|View full text |Cite
|
Sign up to set email alerts
|

Total phenol, flavonoid, proanthocyanidin and vitamin C levels and antioxidant activities of Mauritian vegetables

Abstract: Ten Mauritian vegetables, broccoli, cauliflower, white cabbage, lettuce, Chinese cabbage, mugwort, carrot, onion, tomato and chilli pepper, were analysed for their total phenol, flavonoid, proanthocyanidin and vitamin C contents and antioxidant capacity. Antioxidant activities of the vegetables ranged from 0.43 to 3.68 µmol g −1 fresh weight Trolox equivalent antioxidant capacity (TEAC) and from 0.60 to 8.47 µmol g −1 fresh weight ferric reducing antioxidant power (FRAP). Levels of total phenols in the vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
186
3
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(225 citation statements)
references
References 64 publications
(46 reference statements)
18
186
3
6
Order By: Relevance
“…In the present study, quercetin was the predominant flavonol in cauliflower curds (Table 5). This is in agreement with data reported by Puupponen-Pimiä et al (2003), Bahorun et al (2004), Ahmed and Ali (2013) and Dos Reis et al (2015). Other authors obtained contradictory results (Pellegrini et al 2010;Mazzeo et al 2011;Sikora et al 2012).…”
Section: Phenolic Compoundssupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, quercetin was the predominant flavonol in cauliflower curds (Table 5). This is in agreement with data reported by Puupponen-Pimiä et al (2003), Bahorun et al (2004), Ahmed and Ali (2013) and Dos Reis et al (2015). Other authors obtained contradictory results (Pellegrini et al 2010;Mazzeo et al 2011;Sikora et al 2012).…”
Section: Phenolic Compoundssupporting
confidence: 94%
“…However, other researchers observed significantly lower kaempferol content (Bahorun et al 2004;Pellegrini et al 2010;Mazzeo et al 2011;Sikora et al 2012). According to Kaur et al (2007) and Luthria (2009), the differences reported in the levels of phenolic compounds could be due to the methods used.…”
Section: Phenolic Compoundsmentioning
confidence: 87%
“…Total flavonoids (TFC) were estimated according to the method described by Bahorun et al (2004). One milliliter of sample was mixed with 1 ml 2% AlCl 3 ×6H 2 O.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Bark of C. fistula contains tannins, flavonoids, glycosides, phenolic compounds, carbohydrates, steroids and triterpenoids 3 . Stem bark of C. fistula is potential source of lupeol, ß-sitosterol and hexacosanol 4 . Two new furanoflavones A and B with 3,4'-dimethoxy-5-hydroxy-7, 8 (2"-(2 hydroxyethyl)furan)-flavones,3,4'-dimethoxy-5-hydroxy-7,8-(2"-ethyl furan) flavone,furano-(2",3":7,6)-4'-hydroxyflavanone, pachycarin D, 5-hydroxy-2"-isopropenyl 3 methoxyfurano-(2",3":7,8)-flavone and 5 hydroxy-2"-(1-hydroxy-1methylethyl)-3methoxy-furano (2",3": 7,8)-flavone was identified in 70% aqueous acetone extract of stem of C. fistula 5 Chronic infection caused by parasitic helminthes (Worms) children often becomes infected with one or more species.…”
Section: Introductionmentioning
confidence: 99%